Pengaruh Pemupukan Urea dan Nitrogen Slow Release Terhadap Pertumbuhan dan Kualitas Rumput Lapangan Golf - Nizar Nasrullah; Ni Ketut Wuri Tunggalini (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2000)
The objectives of this study is to investigate the effect of (Urea) and Polymer Coated Urea (Slow Release N - Fertilizer) on the growth and quality of turf Bermuda grass (Cynodon dactylon var. Tifdwarf.) and to find the optimum rate. Treatments are urea and PCU rate at 4.5 g, 9.0g and 13.5 g N/m2/application, respectively. The experiment was arranged in Randomized Block design with 3 replications. Fertilizers were applied 6 times in every 2 locals. The result showed that in the end of the experiment, the higher values of grass height. number of shoots resiliance. Fresh and dry weight were obtained with PCU /3.5 g N/m2/application. The highest dosage of PCU resulted d the highest quality of turf grass. Key words: Urea, Polymer Coated urea, Bermuda grass